Automated clean up method for the determination of PCDD/Fs in long term MSWI emissions. Issue 5 (February 2019) - Colombo, Andrea; Lodi, Marco; Caimmi, Simone; Rossetti, Gianluca; Manni, Andrea
Abstract: The aim of the present work is to assess a simplified and automated clean up procedure for the determination of PCCD/Fs from MSWI emission samples obtained from long term monitoring system. Results showed that extraction recoveries satisfactorily fulfill the criteria required by the official methods for the determination and quantification of PCDD/Fs from MSWI emissions.